Growth and metabolic functions of Schizolobium amazonicum subjected to nickel doses - L. D. Souza; C. Tavares-Drago; B. N. M. S. Rosa; J. P. Teixeira; T. M. Silva; L. F. Gonçalves; L. R. Silva; V. K. C. Ribeiro; T. J. M. Oliveira; V. R. Nascimento; A. E. A. Brito; G. A. S. Nogueira; et al. (Brazilian Journal of Biology)
Abstract Anthropic activities such as industries, agriculture and mining has generated public concern for its numerous irregular disposals of its waste, the incorrect deposition of heavy metals such as nickel (Ni) has caused the degradation and contamination of groundwater and water. Studies that point out cheap and efficient solutions have been an obstacle to the advancement of solutions for degraded area recovery programs. For this, a vegetable home experiment was developed, with an entirely randomized design with 5 treatments being a control (no metal) and 4 nickel concentrations (200 μM/L; 400 μM/L; 600 μM/L and 800 μM/L) with 6 repetitions. The variables analyzed were growth and biochemical activity. Plant height and diameter were not affected by increasing nickel concentrations and this response was due to the low leaf and leaflet production capacity of the species under these conditions, consequently reducing biomass production. Metabolic parameters such as sucrose, carbohydrates, proline and glycine increase under stressful conditions, which does not occur for nutritional configurations that decrease with increasing nickel stress.